An Integral Approach to the Meaning of Competence - Kubova-Semaka, Julija (Vilnius University Open Series, 2020)
Interest in the concept of competence is becoming crucial, as it is highly interconnected with the idea of life-long education and the requirement of continuing professional development. Improving competence and becoming a long-life learner are essential components of ensuring employability. From an educational perspective, a competence-based education addresses the problem of defining exactly what competence is due to the variety of interpretations of its meaning. On the one hand, the concept of competence is understood as an intermediate level of knowledge and skills developed in the future professional (the current student), and yet conversely competence implies efficient behavior in a non-standard situation that requires the highest level of knowledge, skill, and qualification. This paper is based on the analysis of the concept of competence and the variety of interpretations of its meaning. The goal of the paper is to discuss the different concepts of competence, seeking an integral approach to the meaning of competence. The literature review allowed the authors to conclude that the discourse that surrounds competence is widely analyzed in the scientific literature, and the meaning of competence depends upon the approach chosen. Each of these interpretations are rational, and majority of them resonate with Westera’s competence model. According to this model, competence can be considered to be comprised of an individual’s knowledge, experience, skills, abilities, attitudes, values, and other personal qualities that determine understanding and willingness to solve a concrete intellectual or practical challenge, and ensure success. An individual’s competence depends not only on what qualities they have as a whole (their “quality pool”) but also, most importantly, on the structure of qualities that they choose from their inner “pool” to solve a situation in life or in work. Attitudes and values are the bases of competence, which constitutes an action’s driving force and forms both commitment to an activity and confidence in its success. Competence has a dynamic structure, as in every activity a person not only makes decisions but learns in parallel, and as such their knowledge, experience, and skills are enhanced.
Keywords: competence; competency; life-long learning